Structural Insights into the Trp‐Cage Folding Intermediate Formation. Issue 8 (14th January 2013) - Rovó, Petra; Stráner, Pál; Láng, András; Bartha, István; Huszár, Kristóf; Nyitray, László; Perczel, András
Abstract The 20 residue long Trp‐cage is the smallest protein known, and thus has been the subject of several in vitro and in silico folding studies. Here, we report the multistate folding scenario of the miniprotein in atomic detail. We detected and characterized different intermediate states by temperature dependent NMR measurements of the 15N and 13C/15N labeled protein, both at neutral and acidic pH values. We developed a deconvolution technique to characterize the invisible—fully folded, unfolded and intermediate—fast exchanging states. Using nonlinear fitting methods we can obtain both the thermodynamic parameters (ΔHF–I, TmF–I, ΔCpF–I and ΔHI–U, TmI–U, ΔCpI–U) and the NMR chemical shifts of the conformers of the multistate unfolding process. During the unfolding of Trp‐cage distinct intermediates evolve: a fast‐exchanging intermediate is present under neutral conditions, whereas a slow‐exchanging intermediate‐pair emerges at acidic pH. The fast‐exchanging intermediate has a native‐like structure with a short α‐helix in the G11–G15 segment, whereas the slow‐exchanging intermediate‐pair presents elevated dynamics, with no detectable native‐like residue contacts in which the G11P12 peptide bond has either cis or trans conformation. Heteronuclear relaxation studies combined with MD simulations revealed the source of backbone mobility and the nature of structural rearrangements during these transitions. The ability to detect structural and dynamic information about folding intermediates in vitro provides an excellent opportunity to gain new insights into the energetic aspects of the energy landscape of protein folding. Our new experimental data offer exceptional testing ground for further computational simulations.